Cell type-specific targeting with Sindbis pseudotyped lentiviral vectors displaying anti-CCR5 single-chain antibodies - Da Silva, FA (2015)
Lentiviral vectors are among the most efficient tools for gene delivery into mammalian cells. A major goal of lentiviral gene delivery systems is to develop vectors that can efficiently target specific cell types. In the present work, we attempt to genera